AUDIT SISTEM INFORMASI MENGGUNAKAN DOMAIN APO, BAI, & DSS (STUDI KASUS: WEBSITE UNIT PELAKSANAAN TEKNIS PENGEMBANGAN KARIR & KEWIRAUSAHAAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA) - Regina Josephine (2024)
UPNVJ (Universitas Pembangunan Nasional Veteran Jakarta) has established UPT PKK (Unit Pelaksanaan Teknis Pengembangan Karir & Kewirausahaan) as a platform for students to consult and obtain information about entrepreneurship and future career opportunities. UPT PKK UPNVJ is a unit that has a website for information dissemination. However, there are still some aspects on the UPT PKK UPNVJ website that need optimization to fully align with its vision and mission. In essence, this research aims to maximize the services offered by the website features. Therefore, an information system audit is required using the domains of the COBIT 5.0 framework for reliability and validity testing, along with gap analysis calculations, using SPSS (Statistical Package for the Social Sciences). The data for this analysis were obtained from respondents in the UPNVJ environment, particularly UPNVJ students. The domains used include APO, BAI, and DSS. The APO subdomains used are APO01, APO11, and APO13. The BAI subdomains used are BAI02 and BAI09. The DSS subdomains used are DSS01 and DSS03. The research results show that the average capability value obtained is 3.78, corresponding to the Predictable Process level. The gap value obtained from the domains used is 0.14, where only IT processes APO11 and APO13 have a gap of 1 from the expected value of 5.